Crossing of English- speaking expatriates into Galician on Facebook and how their stance taking indexes their identity - Mrozek, Patricia (AUC Knowledge Fountain, 2018)
This study examines the use of linguistic resources to take both affective and epistemic stances by English speaking expatriates currently or previously residing in the autonomous community of Galicia. In turn, I consider what those stances index about the identity of the speakers. The historical background outlines how the Galician code came to become stigmatized. As a stigmatized code, one linguistic resource of particular interest to this study is crossing as defined by Rampton (1999, 2009). Crossing and other linguistic resources used such as metalinguistic talk, become to carry indexes through repeated stance-taking moves. Dubois' (2007) stance triangle is the main tool used for analysis. This study is primarily qualitative in nature, describing how expatriates use the Galician code in order to align and disalign oneself with native Galician speakers. The participants are organized into two groupings: the larger expatriate community which I refer to as individuals, and a community of practice within this larger community. 100 statuses of about 30 participants over a seven-year period were collected, coded and analyzed in order to find major themes and patterns in linguistic resource use. The themes found and linguistic resources used of the expatriates in the community of practice differ from those of individuals. In general, the community of practice was found to use affective stances to create solidarity within group members. Unlike members of the community of practice, individuals within the larger expatriate community were found to use epistemic stance taking moves to demonstrate knowledge about the Galician code through metalinguistic talk. The repeated use of Galician further indicates that in both groups, this code must hold covert prestige over the more prestigious Castilian Spanish.